OPTIMASI DOSIS PEMUPUKAN UREA UNTUK PERTUMBUHAN VEGETATIF CABAI BESAR (Capsicum annuum L.) DALAM POT - Ardani, Windarti; Setiaji, Arkan (BIOMA : JURNAL BIOLOGI MAKASSAR, 2026)
Plants cultivated in pots face limitations in access to nutrients and water, as well as other growth-supporting factors, compared to those planted in the field. Therefore, understanding the plant's response to the potted cultivation model warrants attention. This study aimed to determine the optimal dose of Urea fertilizer that supports the vegetative growth of large chili (Capsicum annuum). Large chili plants of the Panex F1 variety were sown for 28 days and then transplanted into treatment pots arranged in a Randomized Complete Block Design with 4 replications. The treatments consisted of varying urea doses: 0, 1, 3, 5, 7, and 9× the reference dose of 388.5 mg, equivalent to 0 – 3.497 g urea per plant. This fertilizer dose was split into 5 applications via watering over a 40-day growth period. The variables observed were plant height, number of leaves, and shoot dry weight. Analysis of variance results indicated that urea dose variations did not significantly affect plant height and number of leaves but had a highly significant effect on the shoot dry weight variable (p<0.01). Through quadratic regression model analysis (R2=0.305), the optimal urea fertilizer dose for large chili pepper was determined to be 3 grams per plant, with a predicted shoot dry weight of 2.42 grams. Keywords: Kata kunci : large chili pepper, pot experiment, urea nitrogen, vegetative phase